Designing Greedy Algorithm for Cyber Threat Detection - Yogi, Manas Kumar; Aiswarya, Dwarampudi (Journal of ISMAC, 2023)
As the digital landscape continues to expand, the complexity and frequency of cyber threats targeting critical information systems also increases. Effective cyber threat detection has become a paramount concern for safeguarding sensitive data and ensuring the uninterrupted operation of various infrastructures. This research introduces a novel approach to cyber threat detection through the design of a greedy algorithm tailored for identifying specific types of threats. The algorithm focuses on a simplified aspect of threat detection, aiming to highlight the potential of greedy algorithms in contributing to the broader field of cybersecurity. The methodology involves monitoring network traffic for signs of port scanning activity, a common precursor to potential cyber-attacks. The algorithm's effectiveness is evaluated in terms of its ability to accurately identify suspicious scanning behavior while minimizing false positives. By presenting this algorithmic framework, the research aims to contribute to the ongoing efforts in enhancing cyber threat detection techniques.
Keywords: Cyber Security; Privacy; Greedy; Malware; Intrusion; Threat